(5v-9)(8-v)=0

Simple and best practice solution for (5v-9)(8-v)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5v-9)(8-v)=0 equation:


Simplifying
(5v + -9)(8 + -1v) = 0

Reorder the terms:
(-9 + 5v)(8 + -1v) = 0

Multiply (-9 + 5v) * (8 + -1v)
(-9(8 + -1v) + 5v * (8 + -1v)) = 0
((8 * -9 + -1v * -9) + 5v * (8 + -1v)) = 0
((-72 + 9v) + 5v * (8 + -1v)) = 0
(-72 + 9v + (8 * 5v + -1v * 5v)) = 0
(-72 + 9v + (40v + -5v2)) = 0

Combine like terms: 9v + 40v = 49v
(-72 + 49v + -5v2) = 0

Solving
-72 + 49v + -5v2 = 0

Solving for variable 'v'.

Factor a trinomial.
(-8 + v)(9 + -5v) = 0

Subproblem 1

Set the factor '(-8 + v)' equal to zero and attempt to solve: Simplifying -8 + v = 0 Solving -8 + v = 0 Move all terms containing v to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + v = 0 + 8 Combine like terms: -8 + 8 = 0 0 + v = 0 + 8 v = 0 + 8 Combine like terms: 0 + 8 = 8 v = 8 Simplifying v = 8

Subproblem 2

Set the factor '(9 + -5v)' equal to zero and attempt to solve: Simplifying 9 + -5v = 0 Solving 9 + -5v = 0 Move all terms containing v to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -5v = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -5v = 0 + -9 -5v = 0 + -9 Combine like terms: 0 + -9 = -9 -5v = -9 Divide each side by '-5'. v = 1.8 Simplifying v = 1.8

Solution

v = {8, 1.8}

See similar equations:

| ((12v^6)-(14v^3))/(2v^3) | | 2mx^2+3mx=0 | | 2(4x-3)=58 | | 2(x-2)+3x=6x+7-(x-3) | | 15x-220=5x-10 | | 16-11x+12=-16x | | -2x-7+3x=2(5x-9) | | 3e/(e^x) | | 159*200000/X=8.50 | | 2-55m-5=73 | | 32x+48=11-x-7 | | 2(3x-5)=2x-1 | | (2n+6)(4n+2)+16=80 | | 2n^2-40=-11n | | 8n+1=13+2n+8n | | V^2-2vf+f^2=0 | | 3=7cos(2x) | | 3-18x-6=3 | | y=7cos(2x) | | 175+2(100)= | | 9x-124=3x-10 | | 3(2x+5)+3x=42 | | 5(3x-4)-6x=4x+8 | | (7t+6)+(3t+x)+(4t+y)=48 | | t^3+6t-4t-24=0 | | 175.00+3.00x=630 | | X^2-64i^2=0 | | 4+3lnx=17 | | 3p^2-4=p | | 4+3onx=17 | | y/55=11/7 | | 7z-2=3z+8 |

Equations solver categories